GEOLOGY AND THE STUDY OF HEAVY METAL IMPACTS ON ENVIRONMENTAL QUALITY ASSESSMENT USING ARCGIS FOR INTERPRETATION DISTRIBUTION : IN A TRADITIONAL GOLD MINING AREA - Tommy Maulidyanto (Fakultas Teknik Universitas Lambung Mangkurat, 2024)
The Boto area, Jatiroto District, Wonogiri Regency, Central Java, Indonesia, is a traditional gold mining site with inadequate waste management practices, particularly mercury usage. This study aims to assess mercury contamination and evaluate phytoremediation potential in the area. Geological mapping, petrographic analysis, fossil analysis, stereographic analysis, soil Hg measurement, soil and water chemistry analysis, and XRF analysis were conducted to characterize the geology, geomorphology, and heavy metal distribution. The study area is divided into four geomorphological units: Intrusive Hill Unit (V1), Homoklin Hill Unit (S1), Karst Hill Unit (K1), and Alluvial Plain Unit (F1). Stratigraphically, the area consists of the Nglanggeran Breccia Unit interbedded with early Miocene lava, the early Miocene andesite Intrusion Unit with a terrestrial depositional environment, the Wonosari Limestone Unit of Middle-Late Miocene age, and the Holocene Alluvial Deposit Unit. Geological structures include left-lateral normal faults trending relatively north-south (Sesar Boto), left-lateral normal faults trending southeast-northwest (Sesar Brenggolo), and right-lateral downthrown faults trending southeast-northwest (Sesar Mesu). Fractures and veins are also present. Mercury (Hg), manganese (Mn), arsenic (As), and lead (Pb) distribution mapping was conducted. The contaminated zone falls into TCLP-A, and waste management falls into category 1, located in Boto Village, which is a gold mining and processing area. Phytoremediation is proposed as a remediation strategy. Keywords: gold mining, heavy metals, XRF, phytoremediation, distribution